2014
DOI: 10.5430/cns.v2n4p39
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre survey of acute hospital nursing staff training in dementia care

Abstract: Purpose: This paper reports on results of a study to identify education needs of nurses in acute care environments regarding dementia care in Ireland. Method:As part of a multicentre study of dementia prevalence and in-hospital course, a survey was conducted with nurses (n = 151) in six acute hospitals in the south of Ireland. Data were analysed using descriptive statistics. Findings:Despite the availability of a national dementia education programme across all care services, 83% of acute hospital nursing staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
(27 reference statements)
2
25
0
Order By: Relevance
“…An element highlighted from this review was health care professionals' lack of preparation to care for and support acutely unwell patients with cognitive impairment . This is consistent with previous findings, as nurses and doctors have both reported receiving insufficient education and training to support acutely unwell patients with dementia . Traditionally, undergraduate health professional programmes have focused on the medical model of the provision of short‐term interventions related to positive outcomes from an acute medical condition, rather than more complex psychosocial care related to long‐term conditions that also impact on cognition, such as dementia .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An element highlighted from this review was health care professionals' lack of preparation to care for and support acutely unwell patients with cognitive impairment . This is consistent with previous findings, as nurses and doctors have both reported receiving insufficient education and training to support acutely unwell patients with dementia . Traditionally, undergraduate health professional programmes have focused on the medical model of the provision of short‐term interventions related to positive outcomes from an acute medical condition, rather than more complex psychosocial care related to long‐term conditions that also impact on cognition, such as dementia .…”
Section: Discussionsupporting
confidence: 77%
“…32 This is consistent with previous findings, as nurses and doctors have both reported receiving insufficient education and training to support acutely unwell patients with dementia. 42,43 Traditionally, undergraduate health professional programmes have focused on the medical model of the provision of short-term interventions related to positive outcomes from an acute medical condition, rather than more complex psychosocial care related to long-term conditions that also impact on cognition, such as dementia. 16 However, a number of undergraduate programmes have been developed to focus on person-centred care and long-term conditions 44 and more recently in the UK mandatory inclusion of dementia training in all undergraduate health care programmes.…”
Section: Understanding the Current Workforcementioning
confidence: 99%
“…As the initial Barbara's Story was mandatory, its importance to the organisation was conveyed and ensured that staff had to be released to attend. Previous studies have highlighted difficulties in staff being released for non-mandatory training and the need for organisational support and prioritisation (Smythe et al, 2014;Coffey et al, 2014). In the current project, the chief nurse's leadership of Barbara's Story confirmed its high priority in the Trust.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, limited knowledge and understanding of dementia among general hospital staff, coupled with organisational constraints on a busy hospital ward and traditional task approaches to care within acute settings, can contribute to negative attitudes towards people living with dementia and challenges to the ability to provide person-centered care (10,12,19,20). Previous studies have shown that, despite availability of a national education programme specifically for acute hospital staff, the provision and uptake of such education in Irish acute hospitals is poor (14,21) and that staffing levels and lack of resources may be a barrier to staff attending dementia training (14). The Irish National Dementia Strategy (9) has proposed some actions to address the needs of people with dementia in a more responsive and individualised manner.…”
Section: Introductionmentioning
confidence: 99%